First-principles study on the P-induced embrittlement and de-embrittling effect of B and C in ferritic steels. (15th October 2021) - Wang, Jingliang; Enomoto, Masato; Shang, Chengjia
Abstract: First-principles calculations of the Σ5(310) grain boundary in Fe with B, C and P were performed to reveal the mechanism of P-caused embrittlement and de-embrittling effect of B and C. Independent and/or joint effect of B, C and P on the grain boundary energetics and cohesion were determined as a function of concentration. It is found that interstitial segregation sites are more favorable than substitutional sites for all the three elements, and only substitutional P aggravates the grain boundary cohesion, which explains the experimental observation that P only embrittles the grain boundary beyond a critical content. The energetic preference of interstitial B and C makes interstitial P at a disadvantage during the site competition, whereas the de-embrittling cannot be simply explained by the intrinsic strengthening effect of B and C. The influence of these elements on the grain boundary cohesion is further interpreted as a net result of mechanical contribution and chemical contribution, which proved to play the dominant role in the embrittling/strengthening effect of substitutional P and interstitial segregants, respectively. It turns out that replacing part of P atoms by B and C can mitigate the strong mechanical distortion, and thus alleviate the P-caused embrittlement. In the spirit of the Rice-Wang model, we propose a possible method to quantify the variation in chemical bonding upon fracture based on the concept of integral of crystal orbital Hamilton populations (ICOHP). A close relationship was found between the change in total ICOHP of bonds across the grain boundary and the calculated chemical contribution. Graphical abstract: Image, graphical abstract